The Relationship Between Communication Skills and Early Maladaptive Schemas in Pediatric Nurses - Golnaz Mohammadi; Farzaneh Sheikholeslami; MinooMitra Chehrzad; Ehsan Kazemnezhad Leili (Journal of Holistic Nursing and Midwifery)
Abstract Introduction: In nursing, the communication between the nurse and the child is the core of child care. Some barriers can affect the nurse-patient relationship to have proper communication skills for child care. Objective: This study aimed to examine the correlation between communication skills and early maladaptive schemas in nurses working in pediatric wards. Materials and Methods: This is an analytical and correlational study. The participants were 178 nurses working in a children’s hospital in Rasht City, Iran in 2016. The data collection tool was a three-part questionnaire: A demographic form, the interpersonal communication skills scale (ASMA), and the Young Schema Questionnaire-Short Form (YSQ-SF). The collected data were analyzed using descriptive statistics and the Friedman and Spearman tests. Results: The majority of nurses were younger than 30 years (80.8%), had a bachelor’s degree in nursing (89.0%), were married (65.1%), had children (54.8%), were living in urban areas (95.2%), had employment status (63.3%) and less than 15 years of work experience (46.5%). The highest mean scores of ASMA (44.12±0.53) and YSQ-SF tools (2.65±1.04) were related to general communication skills and then disconnection and rejection, respectively. The results of the Spearman correlation test showed that the overall ASMA score had significant negative correlations with early maladaptive schemas of impaired autonomy and performance (r= -0.283), impaired limits (r= -0.421), other-directedness (r= -0.303), and disconnection and rejection (r= -0.302) (P=0.0001). Conclusion: Nurses who have a higher level of early maladaptive schemas showed poorer communication skills. Examining maladaptive schemas in nurses may provide appropriate strategies to improve their communication skills.